Perlindungan Hukum Konsumen Terhadap Pengguna Qris dan Penanganan Penipuan dalam Bertransaksi - Krisma Bima Tara, I Komang; Sudiro, Amad (Universitas Ekasakti, 2023)
In using e-payments such as e-money, it is highly recommended to pay attention to technology that has weaknesses in its technical use. This causes problems regarding the payment system that uses electronic money, especially QRIS, which is becoming increasingly complex so that it demands legal protection with regulations for QRIS users, then also causes the vulnerability of criminal acts of fraud committed in using QRIS. The legal protection that can be given to QRIS user consumers is through preventive legal protection related to digital transactions through the QRIS system carried out with an understanding and awareness for the public regarding the procedures for using the QRIS system in transactions including potential criminal acts. Repressive legal protection is carried out with certain developments by law enforcement officials so that they are ready and alert in the face of criminal acts of digital transactions that utilise the QRIS system. In addition, if the QRIS system is internally problematic, it is necessary to regulate the liability of the QRIS system maker or publisher for the losses incurred. Apply the ITE Law to perpetrators who commit fraud against consumers in transactions using QRIS.